A UPLC-MS/MS method for simultaneous quantification of pairs of oleanene- and ursane-type triterpenoid saponins and their major metabolites in mice plasma and its application to a comparative pharmacokinetic study. Issue 16 (26th February 2018) - Zhao, Wenwen; Liu, Zongyang; Guo, Weiwei; Luo, Kui; Yang, Jie; Gao, Wei; Wu, Xia; Chen, Xiaoqing
Abstract : Pharmacokinetic study of pairs of oleanene- and ursane-type triterpenoid saponins and their major metabolites in control & NAFLD mice. Abstract : Ilexhainanoside D (IhD) and Ilexsaponin A1 (IsA) are a pair of oleanene- and ursane-type triterpenoid saponins, which are also the main bioactive pharmaceutical ingredients of Ilex hainanensis Merr. with great potential to treat non-alcoholic fatty liver disease (NAFLD). The pharmacokinetics of four representative triterpenoids in mice were investigated in this study, which were IhD, IsA and their major metabolites 3β, 19α-dihydroxyolean-12-ene-24, 28-dioic acid (ID) and Ilexgenin A (IA). A sensitive and accurate UPLC-MS/MS method was developed and validated for the simultaneous quantitative determination of IhD, IsA, ID and IA in control and NAFLD mice plasma after oral administration of the total saponins of I. hainanensis (the contents of IhD and IsA were 41.6% and 54.4%, respectively). The results revealed that the pharmacokinetic behaviors could be changed in NAFLD mice compared with control mice. The area under the plasma drug concentration–time curve and maximum plasma concentrations of IhD and IsA were greatly decreased in the NAFLD mice. However, the main residence time of ID and IA were greatly increased in the NAFLD mice. The results revealed that this method could be used to analyze two pairs of triterpenoid isomers in biological samples.